Design and Evaluation of a User-Centered Mobile Application for Elderly Activity Monitoring with Conceptual IoT-Based Emergency Response System - Peter; Yana Erlyana (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
Elderly individuals living independently face increasing safety risks, including medication non-compliance and delayed emergency responses. This study presents the design and evaluation of a user-centered mobile application for elderly activity monitoring supported by a conceptual Internet of Things (IoT)-based emergency response system. The User-Centered Design (UCD) method was applied through five structured phases: empathize, define, ideate, prototype, and test. The design process incorporated survey data from 100 respondents and expert interviews to determine user needs. Key features include medication reminders, emergency buttons, automated alerts, and proposed integration with CCTV for remote monitoring. A system flow diagram was developed to illustrate the conceptual architecture for data communication between users and caregivers. The UI/UX prototype was created using Figma, prioritizing accessibility through high-contrast visuals, enlarged text, and simplified navigation tailored to elderly users. Usability testing using the system usability scale (sus) yielded an average score of 82, indicating excellent perceived usability. These results demonstrate the potential of combining UCD principles with a conceptual IoT framework to enhance home safety for elderly users through responsive mobile technology.